2015
DOI: 10.1155/2015/320386
|View full text |Cite
|
Sign up to set email alerts
|

AngiomiRs: Potential Biomarkers of Pregnancy’s Vascular Pathologies

Abstract: In recent years, microRNAs (miRNAs) have been the focus of research for their role in posttranscriptional regulation and as potential biomarkers of risk for disease development. Their identification in specific physiological processes, like angiogenesis, a key pathway in placental vascular development in pregnancy, suggests an important role of miRNAs that regulate angiogenesis (angiomiRs). Many complications of pregnancy have in common placental vascular alterations, involving an imbalance in the angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
(120 reference statements)
2
4
0
Order By: Relevance
“…Our dual-luciferase reporter system indicated that VEGFA was proven to be a target gene of miR-29b and miR-29 negatively regulated VEGFA . Recent studies noted that the growth factor VEGFA was identified as a target gene of miR-29b, which was consistent with our study [28, 29]. According to Liu et al, miR-29b targeted VEGFA and could be used as novel biomarkers in diagnosis of glioma [30].…”
Section: Discussionsupporting
confidence: 91%
“…Our dual-luciferase reporter system indicated that VEGFA was proven to be a target gene of miR-29b and miR-29 negatively regulated VEGFA . Recent studies noted that the growth factor VEGFA was identified as a target gene of miR-29b, which was consistent with our study [28, 29]. According to Liu et al, miR-29b targeted VEGFA and could be used as novel biomarkers in diagnosis of glioma [30].…”
Section: Discussionsupporting
confidence: 91%
“…We have found that human IUGR is associated with a distinct microtranscriptomic signature, as has been reported in other pathologic pregnancy complications such as pre-term birth, pre-eclampsia, and gestational diabetes [ 21 24 , 62 64 ]. By miRNA microarray, we discovered 141 candidate miRNAs that are differentially expressed in the placenta associated with a cohort of SGA and IUGR neonates compared to their AGA counterparts.…”
Section: Discussionsupporting
confidence: 68%
“…For this reason, integrated assessment of early pregnancy should evaluate a combination of biomarkers and ultrasound [6873]. In addition, we take the opportunity to stress how future investigations about miRNA levels in both sera and placentas should evaluate the possible overlapping among preeclampsia, FGR, and gestational diabetes, since they all have in common placental vascular alterations due to angiogenic disbalance [74]. …”
Section: Discussionmentioning
confidence: 99%